Marketing Mechanisms for Increasing Product Sales of Bisan Snack MSME in Gandasoli Village, Kuningan Regency - Bitticaca, Albert Benaya Tomatoto; Leonardo, Catherine Elizabeth; Ananda, Dea; Neko, Jovan Engelbert; Safriyana (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
MSMEs are the backbone of the economy, playing a crucial role in maintaining economic stability. The success of MSMEs is closely linked to the ability of business owners to innovate and adapt to changes. One promising innovation is the use of social media as a marketing tool. However, many MSMEs, including Bisan Snack, have yet to fully utilize platforms like TikTok and Instagram. This research aims to address this gap by providing intensive socialization on digital marketing to help MSMEs become more productive and relevant to current trends. The study combined interviews, observations, and documentation to carry out the activities, which involved introducing the basics of digital marketing, mentoring in creating TikTok and Instagram accounts, and developing tailored marketing strategies. The results showed that using feeds on these platforms significantly increased the visibility of Bisan Snack products, attracting consumers not only locally but also from other regions. This socialization opened the insights of MSME actors and motivated them to adopt digital marketing strategies. In conclusion, digital marketing, especially through TikTok, has great potential to enhance MSMEs’ competitiveness and productivity, enabling them to reach a wider market and increase revenue.